The Influence of Service Quality and Promotion on Consumer Interest at PT Parahyangan Golf Club, West Bandung District - Meli Mulyani (International Journal of Economics, Commerce, and Management, 2024)
Service companies tend to play the Quality of Service, Promotion and competency of employees to be more skilled in acting as employees who care about the needs and help the difficulties of consumers or customers. This is also supported by one of the factors of a fun playground along with other supporting infrastructure. The purpose of the study is to determine the influence of service quality and promotion on Consumer Interest in Parahyangan Golf Club. Descriptive and associative research methods. This research unit at PT. Parahyangan Golf Club, West Bandung Regency, West Java. The population is 200 athletes. The sampling technique is a census. The duration of the study is 6 months from January to July 2024. The results of the descriptive study showed that the variable of service quality showed a very good interval, the promotion variable showed a very good interval. And the Consumer Interest variable shows a very good interval descriptively. The influence of service quality and promotion on consumer interest is 26%.